INVESTASI PADA REKSADANA SYARIAH DI INDONESIA - Dery Ariswanto (Jurnal Ilmu Akuntansi dan Bisnis Syariah (AKSY), 2020)
This article has the purpose to explain and analyze sharia investment activities in Indonesia. Investment has become one of the most popular economic activities in several developed countries, so far it has been common in developing countries, such as Indonesia. Islamic mutual fund is an interesting activity for people who will invest their wealth on the trading floor in accordance with sharia rules. As Sharia mutual funds are a means or container used to collect funds from the public which will then be invested in a portfolio of securities that is assisted by the investment manager. In this case, the securities portfolio can be in the form of money market instruments, stocks, bonds, or a combination of several forms of them. The operational mechanism in sharia mutual funds consists of two channels, first, the contract between the capital owner and the investment manager is implemented with a wakalah system. Secondly, investment managers and investment users are held in a mudharabah agreement. The basic principle in sharia mutual funds is the mudharabah or qiradh principle, which means an activity in which the capital owner gives a portion of his property to others who are competent to be further managed with the provision that the profits to be obtained from the management results are divided according to the conditions that have been agreed by both parties in advance. Keywords: investment, Islamic mutual funds.